Cholesterol, lipoproteins, and COVID-19: Basic concepts and clinical applications - Kočar, Eva (Biochim Biophys Acta Mol Cell Biol Lipids, 2021)
Cholesterol is being recognized as a molecule involved in regulating the entry of the SARS-CoV-2 virus into the host cell. However, the data about the possible role of cholesterol carrying lipoproteins and their receptors in relation to infection are scarce and the connection of lipid-associated pathologies with COVID-19 disease is in its infancy. Herein we provide an overview of lipids and lipid metabolism in relation to COVID-19, with special attention on different forms of cholesterol. Cholesterol enriched lipid rafts represent a platform for viruses to enter the host cell by endocytosis. Generally, higher membrane cholesterol coincides with higher efficiency of COVID-19 entry. Inversely, patients with COVID-19 show lowered levels of blood cholesterol, high-density lipoproteins (HDL) and low-density lipoproteins. The modulated efficiency of viral entry can be explained by availability of SR-B1 receptor. HDL seems to have a variety of roles, from being itself a scavenger for viruses, an immune modulator and mediator of viral entry. Due to inverse roles of membrane cholesterol and lipoprotein cholesterol in COVID-19 infected patients, treatment of these patients with cholesterol lowering statins needs more attention. In conclusion, cholesterol and lipoproteins are potential markers for monitoring the viral infection status, while the lipid metabolic pathways and the composition of membranes could be targeted to selectively inhibit the life cycle of the virus as a basis for antiviral therapy.